Risky sexual practice and associated factors among HIV positive adults visiting ART clinics in public hospitals in Addis Ababa city, Ethiopia: a cross sectional study - Wondimagegne Belay Tadesse; Abebaw Addis Gelagay (BMC, 2019)
Abstract Background Sexual behavior of HIV positive individuals visiting anti- retroviral clinics is a neglected issue. With access to anti-retroviral treatment, HIV positive individuals experience improved health and are able to reintegrate into their social life and many of them engage in sexual activities. In the context of Ethiopia, safer sex practices among people living with HIV is critical in terms of preventing the acquisition of another strain of HIV and helping address the epidemic. Method An institution-based cross sectional study was conducted at Addis Ababa public hospitals from January to February 2017. A pretested structured questionnaire was used to collect the data. Using the systematic random sampling technique, a total of 562 respondents participated in the study. The data were entered into EPI info version 3.5.3 and transferred to SPSS version 20 for analysis. Descriptive statistics, bi-variate, and multi variable analyses were done. A p-value < 0.05 was considered to determine the statistical significance of the association between factors (independent variables) and risky sexual practice. The Odds ratio was also used to determine the presence and the degree of association between dependent and independent variables. Results A total of 562 respondents participated in the study which revealed that the prevalence of risky sexual practice was 39.1% (95% CI: 35.2, 43.8) three months prior to the data collection. Educational status of participants who were below grade eight (AOR = 2.27, 95% CI:1.01,5.10) and went to grades eight to twelve (AOR = 2.12, 95% CI:1.02,4.41), were married (AOR = 2.07, 95% CI:1.06,4.02), had no concern for safer sexual practice (AOR = 3.74, 95% CI:2.28, 6.13), had CD4 count of ≥500cells/mm3(AOR = 1.66, 95% CI:1.04, 2.64), and used substance (AOR = 3.41, 95% CI:1.83, 6.35) were significantly associated with risky sexual practice. Conclusion The prevalence of risky sexual practice was markedly high in this study due to such contributory factors as low educational status, marriage, lack of concern for safer sexual practices, and substance use.